Comparative experimental and numerical study on energy consumption of track-pin rubber bushing for high-speed tracked vehicles. (November 2019) - Chen, Bing; Zhang, Lijie; Feng, Zhanzong; Du, Yuanyuan; Mo, Wei; Tamma, Kumar K
During the running of high-speed tracked vehicles, the energy loss due to the rotation and tension-compression deformation of the rubber bushing between the track pin and the track plate causes the largest proportion of energy consumption in tracked vehicle propulsion systems; therefore, it is critical to study energy consumption of this component as it is the largest amount of energy loss of the system. First, the theoretical modeling and analysis of the torsional hysteresis and the tension-lag of the hanging glue on the pin of the track pin are conducted. Both energy loss of torsional hysteresis and energy loss of the hysteresis of tension and pressure are obtained when the rubber bushings pass the sprocket, the road wheel, and the idler. Second, a new and novel rubber bushing model based upon the rubber bushing elastic element, the friction element, and the viscoelastic element is proposed. Then the parameters (such as the static elastic stiffness and the maximum friction) of each unit are identified according to the dynamic characteristic experiment. Finally, the numerical simulation results of MATLAB with different stiffness and damping coefficient in addition to tension and compression energy consumption under different frequencies are obtained, and the comparisons are basically consistent with the experimental results; the average errors are less than 8%. The present analytical calculation model is practically useful and can meet the requirements of engineering applications.